The urbanisation of Rome and Latium Vetus from the Bronze Age to the Archaic Era - Fulminante, Francesca 1973- (Cambridge Univ. Press, 2014)
"This book focuses on urbanization and state formation in middle Tyrrhenian Italy during the first millennium BC by analyzing settlement organization and territorial patterns in Rome and Latium vetus from the Bronze Age to the Archaic Era. In contrast with the traditional diffusionist view, which holds that the idea of the city was introduced to the West via Greek and Phoenician colonists from the more developed Near East, this book demonstrates important local developments towards higher complexity, dating to at least the beginning of the Early Iron Age, if not earlier. By adopting a multidisciplinary and multitheoretical framework, this book overcomes the old debate between exogenous and endogenous by suggesting a network approach that sees Mediterranean urbanization as the product of reciprocal catalyzing actions"--
Keywords: Geschichte 1000 v. Chr.-500 v. Chr.; Geschichte 1000 v.Chr.-500 v.Chr.; Cities and towns, Ancient / Italy, Central; Cities and towns / Rome; Urbanization / Italy, Central; Urbanization / Rome / History; Land settlement patterns / Italy, Central / History; Land settlement patterns / Rome / History; SOCIAL SCIENCE / Archaeology; Archäologie; Geschichte; Stadt; Verstädterung; Italy / History / To 476; Italien; Rom; Latium; Hochschulschrift